Harnessing the Power of Long-Range Entanglement for Clifford Circuit Synthesis - Willers Yang; Patrick Rall (IEEE Transactions on Quantum Engineering)
In superconducting architectures, limited connectivity remains a significant challenge for the synthesis and compilation of quantum circuits. We consider models of entanglement-assisted computation where long-range operations are achieved through injections of large Greenberger–Horne–Zeilinger (GHZ) states. These are prepared using ancillary qubits acting as an “entanglement bus,” unlocking global operation primitives such as multiqubit Pauli rotations and fan-out gates. We derive bounds on the circuit size for several well-studied problems, such as CZ circuit, CX circuit, and Clifford circuit synthesis. In particular, in an architecture using one such entanglement bus, we give a synthesis scheme for arbitrary Clifford operations requiring at most $2n+1$ layers of entangled state injections, which can be computed classically in $O(n^{3})$ time. In a square-lattice architecture with two entanglement buses, we show that a graph state can be synthesized using at most $\lceil \frac{1}{2}n\rceil +1$ layers of GHZ state injections, and Clifford operations require only $\lceil \frac{3}{2} n \rceil + O(\sqrt{n})$ layers of GHZ state injections.